Facilitating the sharing of open weather data - Dodds, Leigh (Technical Centre for Agricultural and Rural Cooperation, 2018)
Ensuring that data can be easily accessed, used and shared requires the use of data standards. If you are currently working on a data project you should take time to consider what standards might be available to you to help to achieve the goals of your project.